2006
DOI: 10.5144/0256-4947.2006.439
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters in sick cell anemia patients with and without priapism

Abstract: BACKGROUNDPriapism was associated with certain hematological parameters in sickle cell anemia (SCA) patients in one report but not in another. We studied differences in haematological parameters between SCA patients with and without priapism.PATIENTS AND METHODSEighteen patients with SCA who presented with acute priapism during the years 2001–2004 were compared with age- and sex-matched SCA patients without priapism with respect to hematocrit, reticulocyte count, level of irreversibly sickled cells (ISC), perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
11
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
10
11
3
Order By: Relevance
“…The finding of elevated WBC counts in SCA patients with and without TB was consistent with earlier studies, which showed that leucocytosis was a common feature of SCA even in steady state in the absence of infections and was thought to be due to redistribution of granulocytes from marginal to circulating pool 16,17. However, our data revealed significantly higher mean WBC count among SCA patients with TB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of elevated WBC counts in SCA patients with and without TB was consistent with earlier studies, which showed that leucocytosis was a common feature of SCA even in steady state in the absence of infections and was thought to be due to redistribution of granulocytes from marginal to circulating pool 16,17. However, our data revealed significantly higher mean WBC count among SCA patients with TB.…”
Section: Discussionsupporting
confidence: 92%
“…Thrombocytosis in SCA patients was attributed to the background haemolytic anaemia and autosplenectomy 17,22. However, our data revealed that SCA patients with TB had higher frequency of thrombocytosis and significantly higher mean platelet count than their counterparts without TB.…”
Section: Discussionmentioning
confidence: 99%
“…Nolan et al [ 2 ] reported a positive relationship between priapism and a low Hb concentration as well as high platelet counts, serum AST and bilirubin, but this was not confirmed in our study. The study by Ahmed et al [ 18 ] reported a higher Hb concentration in HbSS patients who had priapism compared to those who did not. There was no significant difference in the Hb concentration of the 2 groups in our study, and this may be partly explained by variations in environmental as well as dietary or other genetic factors which may play an important part in the occurrence of priapism found in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…In two other smaller series comprising 18 and 23 male patients with sickle cell anaemia and a reported history of priapism, study subjects had a higher haematocrit, blood viscosity (Ahmed et al, 2006) and haemoglobin value (Adedeji et al, 1988) compared to age-matched counterparts without this complication.…”
Section: Identification Of Individuals At Risk Of Priapismmentioning
confidence: 98%